Problems in the Field of Emergency Risk Insurance in the Territory of the Republic of Uzbekistan - Makhmudov Alimjon Abdualievich (Genius Publishing Group, 2022)
According to experts, the annual economic damage from the state of emergency restrains the socio-economic development ofboth the regions and the whole country. Currently, the negative processes taking place in the economy require a transition from gratuitous financing of expenses for the elimination of the consequences of emergency situations at the expense of the state budget to oblivion time-based planning and insurance of these expenses. The use of emergency insurance reduces the burden on all other sources of emergency response.
Keywords: Accidents; Load; Economy; Damage To The State